Staying in the game: protective and risk factors for burnout in soccer coaching - Wasielewski, Karol; Szwarc, Andrzej; Wilczyńska, Dominika Maria (Frontiers in Psychology, 2025)
PurposeBurnout is a noticeable problem both in education and in sports. Soccer coach operates in both. The purpose of this study was to investigate how age, coaching experience, education, professional qualifications and professional development -interact to predict burnout among soccer coaches.MethodsThe study sample consisted of 412 participants. Coaches were asked to complete the Soccer Coach Questionnaire, which consists of the following sections: demographic variables, personal development, coaching experience, and satisfaction with salary. Afterwards, they were asked to fill out Link Burnout Questionnaire (LBQ). Statistical analysis was performed in the Automated Statistical Description System (SZTOS).ResultsAge was found to be negatively associated with soccer coaches’ burnout, particularly among those motivated by earning points for license renewal. Also, it was showed that coaching experience is inversely associated with coaches’ burnout, but primarily among those coaches who were motivated by earning education points for license renewal. The satisfaction with salary did not moderate any of the association with measured variables as the authors expected. Among coaches motivated by earning points for license renewal, age was found to be negatively correlated with burnout (p = 0.006). Similarly, coaching experience was shown to be inversely correlated with burnout among coaches motivated by earning points for license renewal (p = 0.008). The effect sizes limit the generalizability of findings. The satisfaction with salary did not moderate any of the association with measured variables as the authors expected.ConclusionThe results suggest that professional burnout may affect younger and less experienced coaches to a greater extent particularly in the context of retraining. Along with age and experience, the rigor of scoring positively affects coaches which suggests a variable pathway of retraining depending on these factors. A greater number of led teams has a positive effect on burnout but not in coaches with higher specialist training suggesting their need for self- actualization and fulfilment. The authors suggest a further need for research into professional burnout in soccer coaches.